2009
DOI: 10.1002/sim.3744
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for the construction of confidence interval for relative risk in stratified matched‐pair designs

Abstract: A stratified matched-pair study is often designed for adjusting a confounding effect or effect of different trails/centers/ groups in modern medical studies. The relative risk is one of the most frequently used indices in comparing efficiency of two treatments in clinical trials. In this paper, we propose seven confidence interval estimators for the common relative risk and three simultaneous confidence interval estimators for the relative risks in stratified matched-pair designs. The performance of the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…RSM-S is a nonlinear method by nature; however, the processes of BS resampling and SOM clustering enable us to deal with the nonlinear BS optimal solutions as if they were parametric parameters. Although percentile method has been reported as a nonparametric method for inferring confidence intervals (Nourissat et al, 2010;Tang et al, 2010), we thought that the parametric approach is more realistic and universal. A previous case study of the preparation of theophylline tablets suggested that the BS resampling technique and SOM clustering are promising tools for evaluating the reliability of nonlinear optimal solutions (Onuki et al, 2008b).…”
Section: Discussionmentioning
confidence: 97%
“…RSM-S is a nonlinear method by nature; however, the processes of BS resampling and SOM clustering enable us to deal with the nonlinear BS optimal solutions as if they were parametric parameters. Although percentile method has been reported as a nonparametric method for inferring confidence intervals (Nourissat et al, 2010;Tang et al, 2010), we thought that the parametric approach is more realistic and universal. A previous case study of the preparation of theophylline tablets suggested that the BS resampling technique and SOM clustering are promising tools for evaluating the reliability of nonlinear optimal solutions (Onuki et al, 2008b).…”
Section: Discussionmentioning
confidence: 97%
“…21 The percentile method is a nonparametric method for inferring CIs. [22][23][24] Consequently, we employed the percentile method as a nonparametric technique.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and Chang (2008) developed four statistics for testing the homogeneity of risk difference in a stratified randomized clinical trial. Tang, Li, and Tang (2010) constructed a confidence interval (CI) of relative risks. Li and Tang (2011) investigated the homogeneity test of rate ratios, and Tang, Zhang, and Li (2013) proposed several methods for testing the homogeneity of risk differences.…”
Section: Introductionmentioning
confidence: 99%